Dampak Literasi Keuangan dan Bias Kognitif terhadap Keputusan Investasi: Sebuah Analisis - Jonathan, Christy; Pradana, Bayu Laksma (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study intends to investigate how financial literacy and cognitive biases, namely overconfidence and availability bias, influence investment decisions in the stock market. Methodology/approach: This research targeted stock investors in Jakarta, accumulating 141 responses via Google Forms survey distributed on social media. Responses were collected between October 2024 - December 2024 using purposive sampling. Data were examined by utilizing SmartPLS 3. Results/findings: The findings reveal that financial literacy and cognitive biases positively influence stock investment decisions. Furthermore, this research also displays that overconfidence bias moderates the relationship between financial literacy and investment decision, exhibiting negative impact. Conclusion: This study concludes that financial literacy and cognitive biases depict a significant role in forming investment decisions, emphasizing the importance for improved financial education to mitigate biases. Limitations: This study concentrates on a particular age group of investors in Jakarta, restricting its generalizability to the broader population of Indonesian investors. Contribution: This study enriches existing literature on investment decisions by highlighting the moderating role of overconfidence bias. Additionally, it underscores the importance of enhancing financial literacy in Indonesia to optimize investment decisions and reduce unnecessary losses.